Hepatitis B Recurrence After Liver Transplantation: A Single Center Experiences and Review the Literature - Dehghani, Seyed Mohsen (Kowsar, 2013)
BACKGROUND: Despite the advances in the treatment of chronic hepatitis B virus (HBV) infection, liver transplantation (LT) remains the only hope for many patients with end-stage liver diseases resulting from HBV. OBJECTIVES: The aim of this study was to investigate the rate of HBV recurrence in cases that had undergone LT due to the HBV related liver cirrhosis. PATIENTS AND METHODS: Forty-nine patients who underwent LT due to HBV related cirrhosis since 2001 to 2009 in Shiraz Organ Transplantation Center were enrolled in the present study. They were asked to complete the planned questionnaire and also to sign the informed consent in order to take part in this study. Post-transplant prophylaxis protocol against HBV recurrence was based on a hundred milligrams of lamivudine daily plus intramuscular injections of hepatitis B immune globulin (HBIG) with appropriate dosage to keep anti-HBs antibody titer above 300 IU/L and 100 IU/L in the first six months and afterwards, respectively. Blood samples were obtained and checked for HBsAg, HBeAg, and the titers of Anti -HBsAb as well as Anti- HBeAb with ELISA. A quantitative HBV DNA assay was also done on all samples (GENE-RAD® Real-time PCR). RESULTS: There were 91.8% males and 8.2% females enrolled in the study. The duration of post-transplant prophylaxis ranged from 3 months to 8 years (mean 18.9 ± 19.3 months). HBsAg and HBeAg were positive in 24.5% and 2% of cases, respectively. Real-time PCR for HBV DNA were zero copies/mL in 91.8% of patients, none of which represented a positive value for HBV recurrence (Positive > 10,000 copies/mL). The mean Anti-HBs Ab titer was 231.7 ± 135.9 IU/L; it was above 100 IU/L in 71.4% of patients. Thirty-seven (75.5%) of the patients were taking tacrolimus plus mycophenolate mofetil, 6 (12.2%) were on cyclosporine plus mycophenolate mofetil, and 6 (12.2%) were taking sirolimus plus mycophenolate mofetil. HBsAg was detectable in seven patients taking tacrolimus plus mycophenolate mofetil (18.9%), in four patients taking cyclosporine plus mycophenolate mofetil (66.7%), and in one patient among the six who were taking sirolimus plus mycophenolate mofetil (16.7%). There was no significant statistical correlation between the presence of a positive value for HBsAg and the immunosuppression regimen or Anti HBsAb titer (P ˃ 0.05). Presence of a positive value for HBsAg was not predictive of a positive HBV DNA or its level in blood (P ˃ 0.05). CONCLUSIONS: Post-transplant HBV prophylaxis with lamivudine and intramuscular HBIG with appropriate dosage to keep anti-HBs antibody titer above 300 IU/L in the first six months and above 100 IU/L afterwards is effective for prevention of HBV recurrence after LT.